REDESAIN PANTI REHABILITASI GANGGUAN JIWA YAYASAN AL-FAJAR BERSERI PENDEKATAN KONSEP EKOLOGI KABUPATEN BEKASI - Idris, Samsul; Soeroso, Yusdianto Haryo; Dewi, Emmi Rostika (Jurnal Pelita Teknologi, 2022)
Human health includes the conditions to meet the body and soul as well as physical health and spiritual health, without healthy conditions people cannot carry out activities as they should. Currently in Indonesia, the number of people suffering from mental disorders is 17% of the 250 million Indonesian population, including patients at Yayasan Al-Fajar Berseri, which continues to increase. disorganized, has little drainage with the potential for flooding during the rainy season, and a lack of inpatient buildings that are beginning to fall into disrepair and look inhumane. Organizing and redesigning the area and building of the Al-Fajar Seri Seri Mental Disorder Rehabilitation House which aims to build an inpatient residence that can accommodate new patients and build humanitarian support facilities. With an ecological concept approach that focuses on biological architecture that is concerned with the health of the population in terms of psychological factors and alternative architecture to produce green areas, in the area of the rehabilitation center there are vegetable and fruit gardens that serve as food for patients to eat, fish ponds that serve as food materials and used for cultivation, livestock sheds, craft studios that function as productive activities that produce, rice paddies and building forms that relate to the form of bow rulers and traditional dog tagog houses that have been transformed into alternative buildings.